2018
DOI: 10.1557/mrc.2018.222
|View full text |Cite
|
Sign up to set email alerts
|

Crack propagation in porous polymer sheets with different pore sizes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…We now discuss the previous results shown in Fig. 1 (c) [21], which is obtained by observing a constant-velocity crack propagation under a fixed strain. By repeating crack-propagation experiments with changing the value of the fixed strain, one obtains the crackpropagation velocity as a function of the given strain.…”
Section: Crack Propagation Test Under a Fixed-grip Conditionmentioning
confidence: 77%
“…We now discuss the previous results shown in Fig. 1 (c) [21], which is obtained by observing a constant-velocity crack propagation under a fixed strain. By repeating crack-propagation experiments with changing the value of the fixed strain, one obtains the crackpropagation velocity as a function of the given strain.…”
Section: Crack Propagation Test Under a Fixed-grip Conditionmentioning
confidence: 77%
“…Considering that the velocity jump has been utilized effectively for developing tough elastomers in the industry, the results of the present study are useful for developing tough polymers in general. This is especially because the previous study [5] suggests theoretically that the velocity jump is expected be observed universally for variety of materials and the previous studies [9] and [8] demonstrate experimentally that the dynamic test is more sensitive for detecting the velocity jump.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, it is reported that the velocity jump is not observed for a semi-crystalline polymer [8] as a result of performing the crack-propagation test under the static boundary condition. However, more recently, the velocity jump is successfully observed for the same semi-crystalline polymer when the crack-propagation test is performed under a dynamic boundary condition [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we did not observe crack propagation in the velocity range studied in the present study. However, in the previous study [33], from a technical reason, the constant-speed crack propagation with a fixed-grip condition was initiated some time after 9 we set a given strain to samples and we consider that the effect of stress relaxation due to this preparation time could tend to suppress crack propagation. This point will be further discussed elsewhere.…”
Section: Discussionmentioning
confidence: 99%